ANALISIS USER EXPERIENCE DAN REDESIGN USER INTERFACE WEBSITE BTA GROUP DENGAN METODE USER EXPERIENCE QUESTIONNAIRE (UEQ) - Ahmad Ibnu Islami (2023)
BTA Group is a business entity that supports the field of education or it can be said that it is a tutoring place for junior and senior middle school students to carry out additional learning in order to better understand the material presented at school. In carrying out learning, of course BTA Group uses a variety of media to support their learning, one of the media used is the BTA Group learning website which is located at www.btagroup.co.id. The website used by the BTA Group certainly has an important role in learning, therefore it is necessary to optimize the website to further maximize the function of the website. The current research has the aim of maximizing the experience provided on the website and also providing an attractive interface for future users. In achieving the research objectives, of course, it is necessary to test the usability of the website to find out the problems that occur. The design will use an approach using the Design Thinking method and in usability testing it will use the User Experience Questionnaire (UEQ) method. The results that will be obtained later, the researcher will provide a new interface display in the form of a prototype which will later serve as an illustration in the development of the BTA Group website.